STRATEGI GURU DALAM MENINGKATKAN HAFALAN AL-QUR’AN SISWA KELAS VIII MELALUI METODE UMMI DI SMPIT TUNAS HARAPAN ILAHI KOTA TANGERANG - nasrullah MA; Erpin Harahap; Shafa Tasya Kamilah; Al-Irsyadiyah; M. Fathi Halimi (Rausyan Fikr : Jurnal Pemikiran dan Pencerahan, 2026)
ABSTRACT Learning the Qur'an is an essential component of Islamic education aimed at developing students' ability to read, understand, and memorize the Qur'an effectively. The success of a Qur'an memorization (tahfidz) program is closely related to the strategies employed by teachers during the learning process. This study aims to describe the strategies implemented by teachers to improve students' Qur'an memorization through the Ummi Method, examine the improvement of students' memorization, and identify the supporting and inhibiting factors in the implementation of Qur'an learning at SMPIT Tunas Harapan Ilahi, Tangerang City. This study employed a qualitative approach using a descriptive method. Data were collected through observations, interviews, and documentation. The research participants consisted of the principal, Qur'an teachers, and eighth-grade students of SMPIT Tunas Harapan Ilahi, Tangerang City. Data were analyzed through data reduction, data display, and conclusion drawing. The trustworthiness of the data was ensured through source triangulation and technique triangulation. The findings reveal that the teachers' strategies for improving students' Qur'an memorization include the use of learning journals as a monitoring tool for students' memorization progress, grouping students according to their abilities into Basic, Middle, and Advanced categories, and implementing the talaqqi method for students requiring intensive guidance. The improvement of students' memorization is supported through regular muroja'ah (revision), continuous motivation, and an acceleration program for students who have not yet achieved the memorization targets. Supporting factors include teachers' certification in the Ummi Method, regular training programs, evaluation meetings, the munaqasyah program, and acceleration programs. Meanwhile, the inhibiting factors identified are the differences in students' initial abilities and the difficulties experienced by some students in balancing academic activities with Qur'an memorization. This study concludes that the strategies implemented by teachers through the Ummi Method effectively and systematically improve the quality of students' Qur'an memorization. Keywords: Teacher Sytagey, Al-Qur’an Memorize, Metodh Ummi, Tahfidz, Islamic Education.